PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 JOMBANG - DIYANTI TRI KARTIKA (Jurnal Pendidikan Ekonomi (JUPE), 2013)
The study of this to determine the effect of study habits and learning environment for student learning outcomes and simultaneous partial. Type of causality research with quantitative approach. This population is all students of 10 grade in SMAN 1. The researche instruments such as questionnaires and data collection techniques through interview and documentation. Statistical traditional method uses regression analysis. Based on a statistical analysis of the data it can be concluded that the study habits and learning environment significantly influence student learning outcomes in the Economics subjects at SMA Negeri 1 Jombang both partially and simultaneously. Keyword: study habits, learning environment and learning outcome.